Thomas Kent letter to Ronald Harms regarding Swainson's Thrush, November 29, 1985 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1985)
Thomas Kent explains why he asks for additional documentation for out-of-season and accidental birds. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed/flatbed